LINKAGE AND INTEGRATION WORK OF COMMUNITY WELFARE NETWORK WITH GOVERNMENT AGENCIES IN UTTARADIT PROVINCE, THAILAND - Utessanan, Chontida; Kunphoommarl, Montri (PEOPLE: International Journal of Social Sciences, 2017)
Community welfare is driven by outside motivation, which results in adaptation of the community to the care of one another in the form of welfare. From this factor, Uttaradit province is awake and developing the model of community welfare. So it brings to overview the work of Uttaradit Community Welfare Fund Network in Thailand (Ut-CWFN). The study was qualitative research. The instrument used in this study was in-depth interview. The objectives of the study were 1) to the process of implementation of (Ut-CWFN) and 2) to pattern of linkage and integration of (Ut-CWFN) by in – depth interviews and participant with 10 keys leader in (Ut-CWFN). Inclusion criteria from the volunteer sacrifice of the previous welfare fund work. And people in the community trust to represent the network. Data analysis by content analysis. The results of the study were as follows: 1) Process driven network of (Ut-CWFN) caused by participation of member, community, private and government. 2) Pattern of linkage and integration of (Ut-CWFN) with associate. The factors listed above to represent the region in driving Community Welfare Fund national policy in Thailand.This study show that mix welfare, integrate, associate and network support to the fund is strong equality and sustainable fund.